Tahap keupayaan pengajaran guru sejarah dan hubungannya dengan pencapaian murid di sekolah berprestasi rendah - Anuar Ahmad,; Siti Haishah Abd Rahman,; Nur Atiqah T. Abdullah, (penerbit ukm, 2009)
The purpose of this study is to determine the relationship between teaching History subject and the students’ performance at five schools that performed poorly in the history subject in SPM. The five teaching aspects are; teachers’ ability (KGS), teaching skills (KMG), teaching methods (TPG), usage of teaching aids (BBM), and teachers’ observation on the students work (PTK). A sample of 436 form five students from the five poorly performed schools in SPM with a minimum mean score of 36.08 and below; in the year 2002 to 2004 was selected as respondents. These five schools are located in Perlis and Penang. The respondents are inclusive of male and female students and Malays and non- Malays students. The instrument used in this study is a set of questionnaire to measure the students’ perceptions regarding the teacher’s performance. The findings show that the KGS and KMG are found to be positive, whereas the TPG, BBM, and PTK are moderately positive. Overall, the students’ perception towards the teacher’s teaching method is moderately positive. The inferential statistics used in this study include Chi-Square Test and t-Test. Chi-Square Test shows that there is no significant difference between the female and the male students, and the Malays and non-Malays students in their History examination results. Whereas the t-Test shows that there is no significant difference between the female and the male students on the perception regarding the teacher’s performance. But there is a significant difference between the Malays and non- Malays students. The correlation analysis shows that there is no significant relation between the teaching aspects and the students’ results except for the teaching skills. This study suggests that it is importance to the schools and teachers to find an approach that will assist the History teachers to improve and vary their teaching skills and consequently produce excellent students in History.